2004
DOI: 10.1259/dmfr/64166944
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral bifid mandibular condyle

Abstract: Bilateral bifid mandibular condyles are rare and may appear as a congenital or developmental anomaly. A case of bilateral bifid mandibular condyles is reported. The patient had no history of trauma and no link was apparent with respect to the patient's medical history. In this case, the condition was an incidental panoramic radiographic finding. Magnetic resonance imaging findings revealed bilateral anterior disc displacement without reduction. The radiographic appearance of this anomaly and the literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
0
21
0
4
Order By: Relevance
“…Most cases of BMCs are asymptomatic and generally diagnosed as an incidental finding during routine radiographic examinations (3,4). With the increased use of panoramic radiographs, investigations of the etiology and epidemiology of BMCs have increased.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of BMCs are asymptomatic and generally diagnosed as an incidental finding during routine radiographic examinations (3,4). With the increased use of panoramic radiographs, investigations of the etiology and epidemiology of BMCs have increased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore dental professionals should have some knowledge of this anatomical abnormality as they mimic fracture/tumor, as well as its implications for function and appropriate treatment [10].…”
Section: Resultsmentioning
confidence: 99%
“…Blackwood examined the developing condylar cartilage of the human fetus and found that it was partitioned by vascularized fibrous septa during the early phase. Persistence of these septa or rupture of blood vessels in the septa was believed to be a cause for development of bifidity [2,9,10]. Blackwood and Moffett have suggested that a retained fibrous septum or a vascular structure impeded the ossification of the mandible, splitting the condyle into two heads [11].…”
Section: Etiologymentioning
confidence: 99%
“…MRI and CT allow detailed visualisation of condylar morphology without osseous overlapping, leading to more accurate and specific diagnosis of some temporomandibular joint (TMJ) conditions 2. CT may also be necessary to avoid mistaking it for a fracture or a tumour, especially in symptomatic cases 3. However, CT does not render a visualisation of the disc or other soft tissues and exposes the patient to various doses of radiation, in contrast to MRI.…”
Section: Introductionmentioning
confidence: 99%